Personal Reflections on Euskaldun (Basque) Men and Matriculture - Otero, Xabi (Matrix, 2025)
In this recorded interview, Xabi Otero offers his personal reflections on being a Basque man and what this means, as well as the role of Basque men in the lives of Basque women. * FORTHCOMING *